From its drifter past to nomadic futures: future directions in backpacking research and practice. (March 2021) - O' Regan, Michael
While the label 'backpacker' didn't originate in 1990 when first presented at an academic conference by the late Philip L. Pearce, its usage rose within an emerging academic discourse community that established shared interests, sources of information, terminology, and methods of communication, along with a certain level of expertise and knowledge on the subject. While the community internationalised and embraced interdisciplinary approaches, a review of the academic scholarship points to the communities increasing instability, as differential authoritative voices conflict over discursive conventions that regulate our understanding of backpacking. While once conceptual and theoretical developments in backpacker research were built through subject level consensus, distinctions within the community point to new hierarchies, with their own particular schools of thought and reinterpretations . As disparities, incongruities and deviations in backpacker research output emerge, this overview explores current research directions and identifies paradoxes, challenges and opportunities that lie ahead.